2002
DOI: 10.1074/jbc.m203870200
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated MAPK Activity Prevents Adipocyte Differentiation of Fibroblasts Lacking the Retinoblastoma Protein

Abstract: A functional retinoblastoma protein (pRB) is required for adipose conversion of preadipocyte cell lines and primary mouse embryo fibroblasts (MEFs) in response to treatment with standard adipogenic inducers. Interestingly, lack of functional pRB in MEFs was recently linked to elevated Ras activity. Ras-dependent signaling plays a significant, although incompletely understood, role in adipocyte differentiation, because activated Ras has been reported to either promote or inhibit adipogenesis depending on the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
5
24
0
Order By: Relevance
“…Thorough research by Tang, Otto, and Lane (58) has provided evidence that clonal expansion is an integral part of the differentiation process and that adipocyte differentiation is prevented in the absence of clonal expansion. However, it has also been reported that clonal expansion, at least under certain conditions, is dispensable (53,54,57). Our finding is compatible with this view, although we cannot rule out the possibility that some ERK1/2 activity remains in the U0126-treated cells, allowing some degree of clonal expansion.…”
Section: Downloaded Fromsupporting
confidence: 82%
See 1 more Smart Citation
“…Thorough research by Tang, Otto, and Lane (58) has provided evidence that clonal expansion is an integral part of the differentiation process and that adipocyte differentiation is prevented in the absence of clonal expansion. However, it has also been reported that clonal expansion, at least under certain conditions, is dispensable (53,54,57). Our finding is compatible with this view, although we cannot rule out the possibility that some ERK1/2 activity remains in the U0126-treated cells, allowing some degree of clonal expansion.…”
Section: Downloaded Fromsupporting
confidence: 82%
“…It is generally agreed that a transient upregulation of ERK1/2 MAPK activity is a prerequisite for clonal expansion and promotes adipogenesis (51-53), whereas sustained activation of the ERK1/2 has been demonstrated to inhibit adipogenesis (54)(55)(56)(57). We show that addition of arachidonic acid enhances ERK1/2 activation following induction of adipocyte differentiation by MDI and prolongs the period during which ERK2, in particular, remains in the active state.…”
Section: Downloaded Frommentioning
confidence: 66%
“…pRB has been shown to promote adipocyte differentiation by enhancing the DNA-binding and transactivation activity of C/EBPb, and/or by inhibiting Ras signaling to suppress the activation of the ERK1/2 MAPKs. 33,34 These findings support our hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…The function of the MAP kinase system in IGF-1 receptor signal-induced 3T3-L1 cell adipogenesis is not clear. It is further complicated by the different effects exhibited by p38 MAP kinase and ERK1/2 on 3T3-L1 cell adipogenesis (5)(6)(7)(8)(9)(10)(11)(12). More molecular studies are required in order to understand the relationship between MAP kinase system and 3T3-L1 cell adipogenesis.…”
mentioning
confidence: 99%